The Posthumanist Valuation of Ecotourism in Mexico from the Environmental Discourses and the History of Mexican Protected Areas - Venegas, Gino Jafet Quintero (2021)
This article presents a historical analysis of the environmental discourses used in the elaboration of conservation and economic use policies regarding Mexican Protected Areas, mainly based on ecotourism. The thesis that these discourses have been built and institutionalized from the discourse of economic development and that, as a result, nature has been objectified to satisfy the economic and recreational needs of the human being is defended. From the posthumanist theoretical perspective, it is concluded that the idea of implementing ecotourism or alternative tourism in Mexico is unethical because it has responded to economic logic, instead of a logic of environmental care and preservation.